INFORMATION ABOUT AUTHORS - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2014)
VANDA ARAMAVIČIŪTĖ – Habilitated doctor of Social Sciences (Education), Professor at the Department of Education, Vilnius University. Research interests: general educology, education and spiritual development of personality, methodology of educational research. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: aramaviciute@gmail.com MARTYNA BAKAITĖ – Master student in Education at Vilnius University. Research interests: adult education, digital culture, language didactics. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: martyna.bakaitė@gmail.com JURATE ČERNEVIČIŪTĖ – Doctor of Humanities (Philosophy), Professor at the Department of Creative Entrepreneurship and Communication, Vilnius Gediminas Technical University. Research interests: communication, cultural and media studies, creative industries, innovations. Address: 26/1 Pylimo Str., LT-01132 Vilnius, Lithuania; e-mail address: jurate.cerneviciute@vgtu.lt MIGLĖ DOVYDAITIENĖ – Doctor of Social Sciences (Education), Lecturer at the Department of General Psychology, Vilnius University. Research interests: consultancy theory and practice, family crises prevention, short-term therapy, conflict resolution. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: migle.dovydaitiene@fsf.vu.lt LILIJA DUOBLIENĖ – Doctor of Social Sciences (Education), Professor and the Head of the Education Department, Vilnius University. Research interests: education philosophy, education policy, multicultural education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: lilija.duobliene@fsf.vu.lt OLGA ILJINA – PhD student of Social Sciences (Education) at the Department of Education, Vilnius University. Research interests: education sociology, social justice in education, grounded theory. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: olgailjina@gmail.com ŽILVINAS JANČORAS – Head of Creative Innovation Lab, Vilnius Gediminas Technical University. Research interests: creative industries, innovations, innovation management, business models. Address: 5-35 Linkmenų Str., Vilnius, Lithuania; e-mail address: zilvinas.jancoras@vgtu.lt ALBINAS KALVAITIS – Doctor of Social Sciences (Sociology), Education Development Centre’s methodologist. Research interests: education sociology, education management, general education. Address: 44 M. Katkaus Str., LT-09217 Vilnius, Lithuania; e-mail address: albinaskalvaitis@gmail.com RUSNĖ KREGŽDAITĖ – PhD student of Social Sciences (Economics); junior researcher at the Creative Innovation Lab, Vilnius Gediminas Technical University. Research interests: creative industries, economics of culture, econometrical analysis. Address: 5-35 Linkmenų Str., Vilnius, Lithuania; e-mail address: rusne.kregzdaite@vgtu.lt ELVYDA MARTIŠAUSKIENĖ – Habilitated Doctor of Social Sciences (Education), Professor at Department of Education, Vilnius University of Educational Sciences. Research interests: general educology, methodology of moral and spiritual research. Address: 39 Studentų Str., LT-08106 Vilnius, Lithuania; e-mail address: martisauskiene@gmail.com VAIDAS MORKEVIČIUS – Doctor of Social Sciences (Sociology), Researcher at the Creative Innovation Lab, Vilnius Gediminas Technical University. Research interests: social survey, social science methods, qualitative comparative analysis, applied statistics and data analytics. Address: 5-35 Linkmenų Str., Vilnius, Lithuania; e-mail address: vaidas.morkevicius@vgtu.lt ŽIGIMANTAS PEČIŪRA – Master student, Department of General Psychology, Vilnius University. Research interests: educational psychology, psychology of career. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: zigpec@gmail.com VAIDA PLATKEVIČIŪTĖ – Student, Department of General psychology, Vilnius University. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania. BIRUTĖ POCIŪTĖ – Doctor of Social Sciences (Psychology), Associate Professor at the Department of General Psychology, Vilnius University. Research interests: educational psychology, psychology of career choice, learning. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: birute.pociute@fsf.vu.lt GIEDRĖ JUDITA RASTAUSKIENĖ – Doctor of Social Sciences (Education), Lecturer at Department of Applied Biology and Rehabilitation, Lithuanian Sports University. Research interests: socioeducational research analysis. Address: 6 Sporto Str., LT-44221 Kaunas, Lithuania; e-mail address:giedre.rastauskiene@gmail.com IRENA STONKUVIENĖ – Doctor of Social Sciences (Education), Associate Professor at the Department of the Education Department, Vilnius University. Research interests: history of education, anthropology of education, education and culture, gender and education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: irena.stonkuviene@fsf.vu.lt ROLANDAS STRAZDAS – Doctor of Social Sciences (Management), Researcher at the Institute of Open Source Research, Associate Professor at the Mechanical Engineering Department, Vilnius Gediminas Technical University. Research interests: innovation management, process improvement, collective creativity, creative industries. Address: 11 Saulėtekio Ave., LT-10223 Vilnius, Lithuania; e-mail address: rolandas.strazdas@vgtu.lt SAULIUS ŠUKYS – Doctor of Social Sciences (Education), Head of the Department of Health, Physical and Social Education, Lithuanian Sports University. Research interests: peculiarities of prosocial children behavior in physical activity. Address: 6 Sporto Str., LT-44221 Kaunas, Lithuania; e-mail address: saulius.sukys@lsu.lt MARIA TILK – Doctor of Social Sciences (Education), Associate Professor at the Department of Educational Sciences, Tallinn University. Research interests: history of education, narrative. Address: Uus-Sadama 5, Tallinn 10120, Estonia; e-mail address: maria.tilk@tlu.ee SVETLANA VASILIONOK – Master student in Education at Vilnius University. Research interests: Lithuanian language teaching in minority schools, Eastern philosophy, the visual arts in teaching and learning. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: svetlana.vasilionok@gmail.com EDITA VAINIENĖ – PhD student of Social Sciences (Education) of Sports and Movement Science Center, Lithuanian Sports University. Research interests: physical culture, identity of specialists of physical education and sports. Address: Sporto Str. 6, LT–44221 Kaunas, Lithuania; e-mail address: editavaina@gmail.com VITA VENSLOVAITĖ – Doctor of Social Sciences (Education), Lecturer at the Department of Education, Vilnius University. Research interests: philosophy of education, musical education, phenomenology in education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: vitavensl@gmail.com CHARL C. WOLHUTER – Professor in Comparative and International Education, North-West University. Research interests: teaching of comparative education, theory of comparative education, teacher education, higher education in Africa. Address: North-West University Private Bag X 6001, Potchefstroom Campus, South Africa; e-mail address: Charl.Wolhuter@nwu.ac.za RIMANTAS ŽELVYS – Habilitated Doctor of Social Sciences (Education), Professor at the Department of Education, Vilnius University. Research interests: education policy, education management, higher education. Address: 9/1 Universiteto Str., LT-01513 Vilnius, Lithuania; e-mail address: rimantas.zelvys@leu.lt